Operational Risk Analysis of Steel Warehouses Using Failure Mode and Effect Analysis (Case Study: PT JKL Cold Rolled Coil Warehouse) - Santosa, Budi; Muttaqin, Prafajar Suksessanno; Sukmawati, Syifa Intan (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2024)
PT. JKL is a subsidiary of PT SBJ (SKJ Group) which is engaged in the logistics or distribution of goods from the port to the customer's warehouse or from the buffer warehouse to the customer's warehouse. One of the services provided by PT JKL is warehouse management for PT SKJ products, namely Cold Rolled Coil (CRC). This research aims to identify risks and causes of risks in cold rolled coil warehouse management operations, so that it can provide suggestions for handling risks in warehouses. This research uses the failure mode and effect analysis method which can identify effects or impacts that are likely to occur in CRC warehouse management. The use of the FMEA method in this research resulted in 7 indicators and 22 sub-indicators of operational risk at the PT JKL warehouse. Apart from that, there are four critical indicators that need to be prioritized because the RPN value is lower than the critical value (70,7). These indicators are supervision of inbound activities (60,85), facilities management (65,17), relationships with other company entities (65,17), and human resource management (22,36). PT. JKL adalah anak perusahaan PT SBJ (SKJ Group) yang bergerak dalam bidang distribusi barang dari pelabuhan ke gudang pelanggan atau dari gudang penyangga ke gudang pelanggan. Salah satu layanan dari PT JKL adalah pengelolaan gudang pada produk PT SKJ yaitu Cold Rolled Coil (CRC). Tujuan penelitian ini untuk mengidentifikasi risiko dan penyebab risiko pada operasional pengelolaan gudang CRC. Metode failure mode and effect analysis (FMEA) digunakan pada penelitian ini untuk mengidentifikasi dampak yang berpeluang terjadi pada pengelolaan gudang CRC. Hasilnya didapatkan 7 indikator dan 22 sub indikator risiko operasional pada gudang PT JKL. Selain itu terdapat 4 indikator kritis yang perlu menjadi prioritas dikarenakan nilai RPN yang lebih rendah dari nilai kritis yaitu 70,7. Indikator tersebut yaitu pengawasan kegiatan inbound (60,85), pengelolaan fasilitas (65,17), hubungan dengan entitas perusahaan lainnya (65,17), dan pengelolaan sumber daya manusia (22,36).